Intelligent multimedia technologies for financial risk management : trends, tools and applications - Grima, Simon; Rawal, Bharat S.; Balusamy, Balamurugan; Özen, Ercan; Goh Guan Gan, Gerald (Institution of Engineering and Technology, 2023)
This book provides an overview of multimedia technologies used in finance and banking, including ML and DL techniques for financial data analysis, fraud and cyber operation countermeasures, concrete applications of NPR for financial data, self-supervised, unsupervised & semi-supervised learning methods and real-world case studies.
4.5.1 What does digital financial inclusion look like?
Keywords: Financial risk management.; Intelligent control systems.; Multimedia systems.; elektronické knihy; electronic books